Back Cover: Luminescent Metal–Organic Framework Sensor: Exceptional Cd2+ Turn‐On Detection and First In Situ Visualization of Cd2+ Ion Diffusion into a Crystal (Chem. Eur. J. 20/2017). Issue 20 (30th January 2017) - Lim, Kwang Soo; Jeong, So Yeon; Kang, Dong Won; Song, Jeong Hwa; Jo, Hyuna; Lee, Woo Ram; Phang, Won Ju; Moon, Dohyun; Hong, Chang Seop
Abstract : A Zn II ‐based metal–organic framework (MOF) serves as an efficient platform for the selective detection of Cu 2+ and Cd 2+ ions over other metal ions. In particular, this framework shows the highest fluorescence enhancement (≈60‐fold relative to Cd‐free MOF) for the hazardous metal ion Cd 2+ among luminescent MOFs. The direct diffusion process of Cd 2+ into the crystal pores could be visualized. More information can be found in the Full Paper by C. S. Hong et al. onpage 4803 ff.